EP347 Preliminary results of primary cancer boost using intensity-modulated radiation therapy for locally advanced cervical cancer. (1st November 2019) - Li, X; Song, Q
Abstract : Introduction/Background: To evaluate the feasibility of primary cancer boost using intensity-modulated radiation therapy in patients with locally advanced cervical cancer. Methodology: From January 1st, 2009 to December 31st, 2012, twenty four cervical cancer patients inappropriate or contraindicated for BT were enrolled. The initial plan was designed to deliver 50 Gy in 25 fractions the pelvic cavity and cervix, followed with an IMRT boost of 26–30 Gy with 2 Gy fraction dose to primary tumor. Most patients were treated with concurrent paclitaxel 50 mg/m 2 and cisplatin 25 mg/m 2 weekly. Results: Of these 24 patients, the median follow-up time was 24 months (ranging from 10 to 44 months). The 3-year overall survival (OS) rate and progression-free survival (PFS) rate was 89.7% and 85%, respectively. Two patients relapsed at 11 and 12 months and died of that, one patient had mediastinal lymph node metastasis at 16 months after definitive diagnosis but is still alive, two patients died of lung metastasis. Acute grade 3 gastrointestinal (GI) occurred in 3 patients (12.5%), and genitourinary (GU) toxicities occurred in 2 patients (8.3%), respectively. Late grade 3 GU toxicity occurred in 1 patient was urinary incontinence. Ten patients had myelosuppression over grade 3. Conclusion: IMRT may be an effective alternative option for cerevical cancer patients unsuitable for BT or in the regions with limited access to interstitial BT. Larger-scale studies are warranted. Disclosure: Nothing to disclose.